Third party ship managers improve the quality of shipping. True? - Tan, Xiao (2016)
The fast raise of third party management in shipping industry is one that cannot be disregarded. Currently, around 20% of the world’s fleet are outsourced to third party ship managers (TPSM), demonstrating the significant market presence of TPSM. To survive and grow sustainably in the shipping market, service quality is needed. Utilizing past studies and research results to examine the current status of TPSM, this paper focuses more on the qualitative aspects of the research topic. The author aims to provide readers with a better view on TPSM services in terms of cost efficiency, technical management and crewing aspects in relation to quality of shipping. More emphasis is placed on the industrial perceptions especially ship owners using interviews, surveys and secondary research methods. A total of 7 in-depth interviews were conducted with professionals from ship owning companies and third party ship management companies. In addition, 133 survey responses were completed with 37 from TPSM, 18 from the ship owning companies who engaged TPSM services and 78 from the ship owning companies who did not engage any services from TPSM. First-hand data collected were utilized in assessing service quality of TPSM for each factor. It was found that TPSM assist in maintaining a minimum shipping standard as required by international regulations. However, limited by the tight management revenue and the intense competition in today’s marketplace, relatively little initiatives for venturing into quality improvements are seen from TPSM. Due to the limited sample size, further studies with larger sample size would be preferred in reducing the potential error and generalizing the findings from this research. Both qualitative and quantitative analysis are recommended to be considered for a holistic understanding of TPSM service quality.